THE EFFECTIVENESS OF THE FREE CIVIL SERVICE EXAMINATION REVIEW PROGRAM ON THE PRE- AND POST-TEST MODEL OF REVIEW ATTENDEES’ PERFORMANCE (Proceedings of the International Conference on Future of Education, 2024)
employees when the majority had formal schooling more than years ago. Also, due to time constraints and a large amount of material to be covered, providing feedback for examination takers before and after lectures can help inform lecturers about the level of knowledge gained by them and improve the effectiveness of their lectures in the next waves of the CCC-CGCs joint free civil service review program. The study aims to determine the extent of knowledge gained by civil service examination takers through pre- and post-test-based examinations. The original 303 registered participants in the program were deduced to 261 who completed the 8-Saturday Review program and voluntarily took the post-test examination. Parallel tests were given at the beginning and end of the program to assess the effectiveness of the didactic lecture. There is a significant increase in scores after the review session at p, it meant that the program helped them increase their receptive power through the pre-and post-lecture knowledge.  However, this percentage of scores was not reaching yet the passing score defined by the civil service commission with a mean score of 54% against the national passing standard percentage of 80%. The study looked also at attendance proportion with the (p=0.392; n=261) and hence this factor was not related to the scores they got. Results were analyzed through paired t-test and Pearson correlation along with the Shapiro-Wilk p-value of 0.934. This joint project is of great help to the prospective takers of the civil service commission examination and recommended continuing the project initiated by the City College of Calamba (CCC) supported by the City Government of Calamba (CGC).
Keywords: pre-and post-test, civil service review, local government unit, community extension